The effect of lignin photodegradation on decomposability of Calamagrostis epigeios grass litter - Frouz, Jan; Cajthaml, Tomáš; Mudrák, Ondřej (Biodegradation, 2011)
The common grass Calamagrostis epigeions produces a large amount of dead biomass, which remain above the soil surface for many months. In this study, we determined how exposure of dead biomass above the soil affects its subsequent decomposition in soil. Collected dead standing biomass was divided in two parts, the first one (initial litter) was stored in a dark, dry place. The other part was placed in litterbags in the field. The litterbags were located in soil, on the soil surface, or hanging in the air without contact with soil but exposed to the sun and rain. After 1 year of field exposure, litter mass loss and C and N content were measured, and changes in litter chemistry were explored using NMR and thermochemolysis-GC-MS. The potential decomposability of the litter was quantified by burying the litter from the litterbags and the initial litter in soil microcosms and measuring soil respiration. Soil respiration was greater with litter that had been hanging in air than with all other kinds of litter. These finding could not be explained by changes in litter mass or C:N ratio. NMR indicated a decrease in polysaccharides relative to lignin in litter that was buried in soil but not in litter that was placed on soil surface or that was hanging in the air. Thermochemolysis indicated that the syringyl units of the litter lignin were decomposed when the litter was exposed to light. We postulate that photochemical decay of lignin increase decomposability of dead standing biomass.
Keywords: Photolysis; plynová chromatografie s hmotnostně spektrometrickou detekcí; lignin; dusík; Oxygen; Poaceae; biomasa; půda; uhlík; lipnicovité; Magnetic Resonance Spectroscopy; aerobióza; světlo; Biodegradation, Environmental; biodegradace; fotolýza; Gas Chromatography-Mass Spectrometry; ekosystém; magnetická rezonanční spektroskopie; Ecosystem; Biomass; Light; Nitrogen; kyslík; Lignin; analýza hlavních komponent; Principal Component Analysis; Aerobiosis; Carbon; Soil